1999
DOI: 10.1074/jbc.274.18.12278
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction of the Cytoplasmic Domain of Triadin with the Skeletal Ryanodine Receptor

Abstract: Triadin has been shown to co-localize with the ryanodine receptor in the sarcoplasmic reticulum membrane. We show that immunoprecipitation of solubilized sarcoplasmic reticulum membrane with antibodies directed against triadin or ryanodine receptor, leads to the coimmunoprecipitation of ryanodine receptor and triadin. We then investigated the functional importance of the cytoplasmic domain of triadin (residues 1-47) in the control of Ca 2؉ release from sarcoplasmic reticulum. We show that antibodies directed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 37 publications
0
78
0
2
Order By: Relevance
“…What is more surprising is the major effect of Trisk 95 overexpression on skeletal E-C coupling compared with the lack of effect related to Trisk 51 overexpression. Both proteins are present in equivalent amount in rat skeletal muscle (10), both are associated with RyR, and they both have the same important RyR-interaction domains previously identified, the N-terminal cytoplasmic domain (19) and the KEKE region (37). Nevertheless, as these two proteins do not have the same function, this may suggest that the functional regulation of RyR by triadin does not involve these interaction domains.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…What is more surprising is the major effect of Trisk 95 overexpression on skeletal E-C coupling compared with the lack of effect related to Trisk 51 overexpression. Both proteins are present in equivalent amount in rat skeletal muscle (10), both are associated with RyR, and they both have the same important RyR-interaction domains previously identified, the N-terminal cytoplasmic domain (19) and the KEKE region (37). Nevertheless, as these two proteins do not have the same function, this may suggest that the functional regulation of RyR by triadin does not involve these interaction domains.…”
Section: Discussionmentioning
confidence: 50%
“…In skeletal muscle, triadin has been shown to inhibit the calcium channel activity of purified RyR (18,19). These experiments were the first to identify a function of triadin in skeletal muscle, and they led to the conclusion that triadin could regulate RyR function via inhibition of the channel.…”
Section: In Skeletal Muscle Cells Excitation-contraction (E-c)mentioning
confidence: 94%
“…Although originally thought to be the link between RyR1 and DHPR (6 -8) and a key modulator of EC coupling (9 -11), it appears evident now that triadin acts primarily as a negative regulator of RyR1 activity (12)(13)(14)(15). Although the mechanism by which triadin regulate RyRs remains unclear, there is support for the hypothesis that triadin is involved in facilitating the cross-communication be-tween calsequestrin (CSQ) and the RyRs (16 -18).…”
mentioning
confidence: 88%
“…We do not yet understand the role of HRC, as the more abundant Ca 2ϩ -binding protein calsequestrin appears to serve its role as a Ca 2ϩ store perfectly well. It was shown that calsequestrin plays a role in the regulation of the ryanodine receptor (28,29) in addition to the Ca 2ϩ store function. Thus, HRC may perhaps also have a regulatory role.…”
Section: Discussionmentioning
confidence: 99%